2020
DOI: 10.36659/dae.2020.045
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade do serviço de abastecimento de água em Campina Grande-PB com o uso de indicadores, incluindo o de satisfação dos usuários

Abstract: Entre os desafios enfrentados pelas concessionárias responsáveis pelo abastecimento de água nos centros urbanos está a prestação de um serviço de qualidade que atenda às exigências dos usuários. Objetivando colaborar com a melhoria do serviço de abastecimento oferecido à população, o presente trabalho propôs o desenvolvimento de um índice de desempenho do serviço de abastecimento de água na cidade de Campina Grande - Paraíba (IDSA-CG). Foram estudados 22 indicadores divididos em cinco categorias: operacional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To prepare the water with electrical conductivity of 4.0 dS m -1 , the soluble salts NaCl, CaCl 2 .2H 2 O, and MgCl 2 .6H 2 O were used in an equivalent ratio of 7:2:1 (Medeiros, 1992) between Na, Ca, and Mg, respectively, following the relationship between ECw and its molar concentration (mmol c L -1 = EC x 10).…”
Section: Methodsmentioning
confidence: 99%
“…To prepare the water with electrical conductivity of 4.0 dS m -1 , the soluble salts NaCl, CaCl 2 .2H 2 O, and MgCl 2 .6H 2 O were used in an equivalent ratio of 7:2:1 (Medeiros, 1992) between Na, Ca, and Mg, respectively, following the relationship between ECw and its molar concentration (mmol c L -1 = EC x 10).…”
Section: Methodsmentioning
confidence: 99%
“…The water supply of 0.8 dS m -1 (Table 2) was stored in 500-L water tanks and used to prepare the 3.0 dS m -1 saline solution, made with sodium chloride (NaCl), calcium chloride (CaCl 2 .2H 2 O) and magnesium chloride (MgCl 2 .6H 2 O) in the proportion of 7:2:1 (Medeiros 1992), and maintaining the ratio between the water electrical conductivity and the molar concentration (mmol c L -1 = EC × 10). OM: organic matter; SB: sum of bases; ESP: exchangeable sodium percentage; ECse: electrical conductivity of the soil saturation extract.…”
Section: Methodsmentioning
confidence: 99%
“…The lowest salinity water (0.3 dS m -1 ) came from the local water supply. The 3.0 dS m -1 saline solution was prepared by adding sodium chloride (NaCl), calcium chloride (CaCl2.H2O) and magnesium chloride (MgCl2.6H2O), in the proportion of 7:2:1, respectively (Medeiros, 1992), to the supply water, in order to obtain the desired electrical conductivity, according to the ratio between ECw and its concentration (mmolc L -1 = EC × 10), according to Richards (1954). The highest salt level of the water tested in this research is commonly observed in the semi-arid region of Northeast Brazil.…”
Section: Methodsmentioning
confidence: 99%